하악에 발생한 저등급의 점액섬유육종: 증례보고 - 박지훈(Ji-Hoon Park); 최소영(So-Young Choi); 권대근(Tae-Geon Kwon); 김진수(Chin-Soo Kim) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2011)
Myxofibrosarcoma, also known as a myxoid variant of a malignant fibrous histiocytoma (MFH), is one of the most common sarcomas in the extremities of elderly people. The lesion is characterized by a high frequency of local recurrence but is uncommon in the head and neck regions. Low-grade myxofibrosarcoma, which is commonly misinterpreted as being benign, has a tendency for histological and biological progression in local recurrences, highlighting the importance of an accurate diagnosis and wide surgical excision of the primary lesion. We report a rare case of low-grade myxofibrosarcoma of the mandible located in the left mandibular body and angle area. The tumor was first diagnosed as a myxofibroma and was resected initially. After the final biopsy the patient underwent combined chemo-radiotherapy. The progress of the patent was uneventful until the one year follow up. KCI Citation Count: 0